How and Why Should We Study Religions in the Age of Globalisation? - Hutter, Manfred (Chonggyo wa munhwa, 2020)
Modern society has been changing over the last decades. Such changes also affected religions and the study of religion. Some scholars speak of a cultural turn which means a shift in studying religions from a purely philological point of view to looking at them in a broader way–by also taking religious practices, rituals, and behaviour into account, instead of dogmatic teachings only. Scholars of religion should always try to present a balanced view: taking into account a traditional approach which always focusses on the historical and/or contemporary spread of a certain religion, while also asking about challenges religions are faced with in a globalised world with its social changes–thus respecting this cultural turn. Viewing religions from the one side, we may use the label Words and exemplify this with a short description of religious plurality in Germany, and viewing religions from the other side we may use the label Humans to illustrate this with several examples of modern challenges of religions.